Anti-Corruption Activities – Chosen Examples - Kubiak, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Corruption is a long-lasting phenomenon that still exists in many countries and societies. In Poland and in many different countries it is perceived as an important social problem. Various actions are undertaken to reduce and counteract corruption. One of the examples of such actions is the formulation and implementation of the anti-corruption strategy between 2001-2009, and the preparation of the next stages of its implementation between 2010-2015. It is important to investigate which procedures were formulated and implemented as a part of the strategy. The Stefan Batory Foundation’s Anti-Corruption Program monitored the implementation of the strategy by conducting sociological research in 65 central and regional (voivodeship) institutions, city councils, customs offices and tax offices. By applying different research techniques (in-depth interviews, observations, document analysis, postal surveys and internet surveys) the aims were: to determine what procedures and anti-corruption actions were undertaken in these institutions, what training was conducted, if and how the ethical advisors were functioning, and which of the institutions’ own anti-corruption initiatives were introduced.